(untitled) - PRIYO UTOMO, TOMY (Language Horizon: Journal of Language Studies, 2014)
Social Class in Arundhati Roy’s The God of Small Things TomyPriyoUtomo English Literature Faculty of Languages and Arts State University of Surabaya tomy.priyo@gmail.com Prof.Dr. FabiolaDharmawatiKurnia, M.Pd. English Department Faculty of Languages and Arts State University of Surabaya fabkurnia@gmail.com Abstrak Karyasastraadalahrepresentasikehidupansosial.Di dalamkehidupanmasyarakattertentu, seperti India, adasebuah system yang dinamakankelassosial.Kelassosialmembawamasalahsebagaidampak yang tereflekisdalam novel The God of Small Things karyaArundhati Roy.Tujuandaripenelitianiniadalahuntukmengungkappenggambarankelassosialpadatokoh-tokohdandampaknya.Dalamskripsiini, data yang digunakanadalah novel The God of Small Things karyaArundhati Roy yang diterbitkanpenerbit Flamingo.Dalammenyelesaikanmasalah yang sudahdipaparkan, penggunaanteorikelassosialmilik Karl Marx akandiaplikasikan. Penggambarantokoh-tokohkelassosialdianalisadenganmenggunakandefinisikelas yang didukungolehpelbagaiaspeknya.Sedangkandampakdarikelassosialdianalisadenganmenggunkankonsekuensidarikonsepkelassosial.Tokoh-tokohsosialkelasdigambarkanmelaluibeberapapoin yang mencangkupkekayaan, pekerjaan, danpendidikan.KelassosialatastergambarpadasosokPappachi,Mammachi, Baby Kochama, danChacko.SedangkanKelassosialbawahtergambarpadasosokAmmu, Velutha, Rahel, danEstha. Olehkarenaitu, kelassosialpadatokoh-tokohtersebutmemeberidampakpadakesehatanfisik, kesehatanjiwa, kehidupankeluarga, pendidikan, agama, dansistemkeadilanpadakasuskriminal.Jadi, halinisepertiduridalamdaging yang sudahmengakarpada system kehidupansosial di India. Hal ininampakpadakasusAmmu yang haruskehilangan status sosialnya, hargadiriPappachiterhadapMammachi, dantokoh-tokohlainnya yang meenghadapimasalahkelassosial. Kata Kunci: India, masyarakat, kelassosial. Abstract Literary work is the representation of social life. In a particular social life, such as India, there is social class. The social class dribbles the ball of problems as the impact in Arundhati Roy’s The God of Small Things is one of the representation of it. This thesis is aimed to reveal depiction of character’s social class and impact of their social class. In this thesis, Arundhati Roy’s The God of Small Things published by Flamingo is used as the main data source. In answering the statement of the problems, theory of social class based on Karl Marx’s view is applied. The depiction of the characters’ social class is analyzed using definition of social class and supported by aspects of social class. The impact of the characters’ social class is analyzed using the consequences concept of social class. The main characters’ social class is portrayed through several points. They are wealth, occupation, and education. The Upper social class is portrayed on Pappachi, Mamachi, Baby Kochama, and Chacko. Then, The Lower Social class is portrayed on Ammu, Velutha, Rahel and Estha. Therefore, social class on the characters gives impact on Physical health, mental health, family life, education, religion and the criminal system justice. So, this thesis portrays the intimate enemy of the system that has been rooting in India that always brings problems caused by it, the social class. It can be looked at the fall of social status of Ammu, the dignity of Pappachi toward Mammachi, and other characters who face the same problem of social class. Keywords: India, society, social class. INTRODUCTION In social life, people are demanded to live in integrated individuals where each individual delivers different characteristics. These differences finally construct a problem within the social life, especially economic problems. Economic problem has been classic problem that cannot be avoided in modern life, thus people are categorized by their capability in economic status or class. This categorizing unconsciously creates a phenomenon where society is sorted. The sort of society based on the economic capability seems to have been articulated by Karl Marx, where society with low capability to product will be dominated by the society with high capability to product. Marx exclusively distinguishes three major classes, each of which is characterized in its role in the productive system by ‘the factor of production’ it controlled –the land-owners, obviously, by their ownership of land; the capitalists (‘bourgeoisie’) by their ownership of capital; and the proletariat (working class) by their ‘ownership’ of their labor-power (Worsley, et al., 1970: 302). Finally, social class turns to be tight and the distance among classes go further. In modernism, construction of society is shaped by the demands to live better. This way indirectly emerges competition that a one should defeat the other one just to earn the economic status. This also becomes the base of Western to colonize and dig the domination to Eastern and African. Indeed, colonization has been passed, and all people has freed, but it has not been clear at all. Behind this fact, colonization has leaved behind the effects toward the people who have been colonized. Sometimes, this fact slaughters keenly the problem of the post-colonized people, for instance in India. In India, there is known system of caste, Brahman, Kshatriyas, Vaishyas, and Sudras. Some 3500 years ago invaders from the north, known as Aryans, imposed the caste system; there is no conclusive evidence that they originated the idea of caste in India, but it seems to be the most likely explanation. The Hindu religion divides the population into five basic groups. The highest groups are known as Varnas (colors) and beneath them come a group without caste, the Untouchables. The four Varnas consist of: Brahmans (a priest caste), Kshatriyas (a military caste), Vaishyas (a merchant or agricultural caste), Sudras (a laboring caste). These caste has been like a stamp to people’s destiny and it impacts to their statues in society. These statues are not decided by what they have economically but from what caste they are. Then, it turns to be interesting thing when this system is faced with the problem of economic in modern life (Nobs, 1980: 30—31). As modern people, ability of delivering feeling is not only through direct utterance. The freedom to think, to articulate what they feel finally reach the world of literacy based on the experiences. In the literacy, meanings are accommodated with the beauty of words. Hence, in literary work, especially novel, the view of society including the problem of class can be mediated. It is added by Richard Taylor’s Understanding the Elements of Literature, he says that literature is art that essentially created by imagination of the author’s experiences (Taylor, 1981: 1). Wellek and Warren even assert that literature can be treated as a document that contains of historical idea and philosophy (Wellek& Warren, 1984: 111). Subsequently, literature work can be something important, crucial, and even interesting thing to dig up with interpretation. The crucial things can be seen in Arundhati Roy’s The God of Small Things. TheGod of Small Things depicted the life Indian society. The setting of the story takes place in Kerala. The story tells us that comunism or even religion which teach us about equality in human rights in the reality it can not change discrimination and patriarchy in society. The main characters in this novel are Estha and Rahel. They are twins. Their grandfather is the owner of a company from Christian which is very high class (touchable). But their mother has marry with the Hindust man, it means she must change become lower class (untouchable). Max Weber stated that the social class is divided into trhree layers- the upper class, the midle class and the lower class. The higest level is held by educated and wealthy family. This includes Pappachi family. Their social classes are in the high social classwhich gives the member of this class has different life styles,attitudes, educations, and opportunities in the society. The next class is lower class (untouchable), untouchable person can not touch high class. They are uneducated person. They are not allowed to work in high position. In this novel untochable personis Velutha. Velutha is a paravan. Paravan is the lowest caste in Indian. Furthermore, the richness of this novel has glimpsed on the awards that attaches on Arundhati Roy herself and hers. It needs to know that The God of Small Things has won The Man Booker Prize for fiction in 1997. Arundhati Roy herself is a famous Indian novelist and social activist. In 2002, she won the Lannan Foundation's Cultural Freedom Award for her work "about civil societies that are adversely affected by the world’s most powerful governments and corporations," in order "to celebrate her life and her ongoing work in the struggle for freedom, justice and cultural diversity”. In 2003, she was awarded 'special recognition' as a Woman of Peace at the Global Exchange Human Rights Awards in San Francisco with Bianca Jagger, Barbara Lee and Kathy Kelly. Roy also was awarded the Sydney Peace Prize in May 2004 for her work in social campaigns and her advocacy of non-violence. In January 2006, she was awarded the Sahitya Academy Award, a national award from India's Academy of Letters, for her collection of essays on contemporary issues, The Algebra of Infinite Justice, but she declined to accept it “in protest against the Indian Government toeing the US line by 'violently and ruthlessly pursuing policies of brutalization of industrial workers, increasing militarization and economic neo-liberalization”. In November 2011, she was awarded the Norman Mailer Prize for Distinguished Writing. It shows that she is one of important writer in India. Her literary works always tell about social and tradition also symbols to be analyzed. In the instance Roy shows Indian culture as the identity in her literary work. Most of her master piece is showed about social class, tradition in Indian culture. She wrote many books such as an ordinary person’s Guide to Empire, War talk, Public Power in the Age of Empire, Power Politics, The Checkbook and the Cruise Missile and The Cost of Living. After all, it is unarguable to be questioned that Arundhati Roy’s The God of Small Things is full of crucial issues. Based on those facts, the crucial issue that emphasizes on this thesis is in the social classes, thus the potential title that can be put on it is “The Intimate Enemy of Social Class in Arundhati Roy’s The God of Small Things”. RESEARCH METHOD The used method is descriptive quality; it means that the essence or the quality of the data becomes the reference to work rather than the quantity of the data. With interpretation toward the data, the analysis can be worked. Interpretation becomes crucial step because with regardless this, the analysis cannot be maximally operated. It is also as the technique of the study. Then, the approach of the analysis sharpens to mimesis where the universe is used as comparative literature toward the result of the analysis. Indirectly, it includes in extrinsic approach where the sociality is referred as the universe. SOCIAL STRATIFICATION In social life, they always have something that is appreciated. That can be wealth, knowledge, education or economic. In Narwoko&Bagong’sSosiologi: TeksPengantardanTerapan, SoerjonoSoekanto states that in rural society, land and livestock are often considered more valuable than education. On the contrary, it does not happen in modern society. In society, people who have valuable goods in large quantities will be more appreciated rather than people who have a small amount. Thus, they will be considered as low class (Narwoko&Bagong, 2004: 152). This low class construction, because there is characteristic of “not” low class. This construction finally creates categorizing that can be called as stratification. Sorokin states that ‘Stratification’ is a term used to characterize a structure of inequality where individuals occupy differentiated structural positions and the positions are situated in layers (or strata) that are ranked hierarchically according to broadly recognized standards. The implied reference to sedimentary layers from geology reflects the relative permanence of the posited structure and the long history that is assumed to have generated it. Stratification researchers focus primarily on the empirical study of the sources of the rankings that generate the hierarchy of strata, the mobility of individuals between strata, and the mechanisms of integration that allow societies to cope with the existence of persistent inequalities between strata (Narwoko&Bagong, 2004: 153). Aristotle observed two millennia ago thatpopulations tended to be divided into three groups: the very rich, the very poor and those between. It shows that in ancient times people have come to know and recognize the hierarchy system in society. Social stratification can basically be distinguished into three kinds. They are Class, Status and Power (Worsley, 1970: 288). SOCIAL CLASS According to Karl Marx’s Theory of Class, as quoted by Chris Livesey, it is stated that class is the motor of social development. Marx argues that society has developed through four main epochs (“period time”). They are Primitive Communism, Ancient Society, feudal Society, and Capitalist Society. For him, only the first epoch (the “primitive communism”) is free from some form of social stratification on the basis of class. This is because, for Marx, class forms of social stratifications only come into existence once people start producing more goods than they require fulfill their everyday needs and gatherer society are basically subsistence societies; that is people can only manage to hunt/ gather enough food for their everyday needs (sociology.org.uk). To describe in detail this theory, it needs to be classified based on the definition, aspect, and consequences of social class. Karl Marx is one of the first writers who analyzes class differences. He sees class as a phenomenon of any society where the ownership of wealth and the means of production, factories or land, gives an economic basis for stratification. Marx also outlines different stages in history in which the ownership of property gives one group control over others. The group, which controls and owns the means of producing food and goods, is the dominant class. Furthermore, Marx argues that there is a constant struggle, a class struggle, and this conflict between the different classes brought about changes in society (Nobs, et al., 1980: 28). Therefore, the conflict among classes are grounded by the domination of a high class over the low class. Class itself, as Lenin says, is large groups of people differing from each other by the place they occupy in a historically determined system of social production, by their relation (in most cases fixed and formulated by law) to the means of production, by their role in the social organization of labor and consequently, and by the dimensions of the share of social wealth of which they dispose and the mode of acquiring it (Collected Works, Vol. 29: 421). Furthermore, Karl Marx divides social class into two classes. They are Capitalist class (or "bourgeoisie") and Working class (or "proletariat"). Capitalist class is those who own and control the means of production (which involves ownership of such things as land, factories, financial institutions and the like). And working class is those who own nothing but their ability to sell their labor power (that is, their ability to work) in return for wages (Henslin. 2003: 284). Similar to Karl Marx in discussing about social class, Max Weber tries to generate it with defining social class as a large group of people who rank close to another in wealth, power, and prestige. These three elements separate people into different lifestyles, give them different chances in life, and provide them with distinct ways of looking at the self and the world (Henslin, 2012: 276). Aspects of socials class are classified referred by wealth, by occupation and by educational level. Each can be used for different purposes or they can be combined (Worsley, 1970: 292). According to Henslin, the primary dimension of social class is wealth. Wealthconsists of property and income. Propertycomes in many forms, such as buildings, land, animals, machinery,cars, stocks, bonds, businesses, and bank accounts. Incomeis money received as wages, rents, interest, royalties, or the proceeds from a business (Henslin, 2003: 276). Furthermore, the spread of material resources among the population is an important indicator of social inequality, while changes in this distribution over time indicate whether society is becoming more or less equal. The investigation of the spread of personal income and wealth, however, is fraught with difficulty because of inaccuracies in the data, the problem of deciding the relevant unit of analysis (whether to use individuals, families or households), how to assess the non-monetary benefits derived from government expenditure, and the way individuals' positions may change over the life-cycle (Abrecombie, 1994: 120). Occupation is another aspect of class that definitely can be included as the ground of belonging to a class.People give less prestige to jobs that are lowpaying, require less preparation or education, involve more physical labor, and areclosely supervised. For example, people in every country rank collegeprofessors higher than nurses, nurses higher than social workers, and social workershigher than janitors. As soon as people develop of being specialized kinds of work, they also get the idea that some kinds of work are more prestige than others. The high prestige occupations generally receive the higherincomes; yet there are many exceptions. The next is factor is education. According to Lindemann, as quoted by Sharon Link & Alexandra Howson in Sociology Reference Guide: Defining Class, it is stated thateducation plays a significant role in one’s social position, that is, to aperson’s place in the social hierarchy and ultimatelyin stratification. Education also can provide equalityof opportunity and contributes directly to social mobility (that is, to one’sability to move upwardly from one’s social class of origin). Social and economic indicators such as income and occupation are typically used to measure social class, and education plays a significant role in determining one’s employability, employment, and income (Danziger& Reed, 1999). Education therefore plays a crucial role in the likelihood of people being able to improve their social class location by moving into higher occupational classes. Education is seen as having different functions. Within a consensus or functionalist perspective, associated with the work of Talcott Parsons, education is seen to have a role in socialization; it contributes to ensuring that children are ‘trained’ to comply with the demands of the social system. Indeed, for many people, education exists to ensure that individuals learn how to be good citizens and thereby maintain an efficient, stable social order. Consequently this view of education emphasizes merit, ability and effort and the needs of society or the economy. Such a view also expresses in the idea that education is about individual opportunity (Raines & McAdams, 2006). When social class exists in society, there will be many impacts given. According to Henslin (2003: 288), consequences of class are divided into six categories. It is very good to be applied as the impact of the social class in The God of Small Things. They are: (1) physical health (2) mental health (3) family life (4) education (5) religion and (6) criminal justice system. SYSTEM OF CASTES IN INDIA India is a country where system of caste grows basically. There were four original castes, separately created by Brahma: Brahmans, Kshatriyas, Vaishyas and Shudras. This fourfold division has its origin in the Vedas, the sacred books of the Hindus, and one of the ‘most ancient books in the library of mankind’. They are admitted by all the adherents of the Hindu system to be the primary and infallible authority on the origin of the castes (Keanne, 1978: 24). Senart defines a caste as a close corporation, in theory at any rate rigorously hereditary : equipped with a certain traditional and independent organization, including a chief and a council, meeting on occasion in assemblies of more or less plenary authority and joining together at certain festivals : bound together by common occupations, which relate more particularly to marriage and to food and to questions of ceremonial pollution, and ruling its members by the exercise of jurisdiction, the extent of which varies, but which succeeds in making the authority of the community more felt by the sanction of certain penalties and, above all, by final irrevocable exclusion from the group. While, according to Sir. H. Risley, a caste may be defined as a collection of families or groups of families bearing a common name which usually denotes or is associated with specific occupation, claiming common descent from a mythical ancestor, human or divine, professing to follow the same professional, callings and are regarded by those who are competent to give an opinion as forming a single homogeneous community (Ambedkar, 1916: 3—5). In India, there is known system of class based on the caste. Thus the caste is having seemed to a thing that is flown in people’s blood. Hindu religion divides the population into five basic groups. The four highest groups are known as Varnas (color) and beneath them come a group without caste, the Untouchables. The four Varnas consist of Brahmans (a priest caste), Ksathriyas (a military caste), Vaishyas (a merchant or agricultural caste) and Sudras (a laboring caste). Within these groups there are thousands of subdivision; among the Brahmans there are more than 500 subdivisions and there are over 200 divisions of people without caste (Nobs, et al., 1980: 31). India's majority population is Hindu (although it is worth noting that Hinduism is highly variable). Caste is often regarded as a social structure arising from Hindu practices and ideas. But, other religious groups in India also make caste distinctions. Muslims, Christians, Sikhs, Buddhists, and Jains have historically recognized and reinforced caste and/or varnadistinctions (Mines, 2009: 67). SYRIAN CHRISTIAN AND KERALA HISTORY Kerala provides a particularly interesting case study on race because religions are divided from each other based on caste. That is, not only do Hindus follow the caste system, but Christians as well (Sonja, 2001: 129).The Syrian Christians pride themselves on being one of the earliest Christians in the world and trace their conversion to the year 52 AD, when the Apostle of Jesus, St. Thomas arrived on the Kerala port city of Malankara near the bustling trade hub, Muziris.19 According to Syrian Christian communal history, after the death of Christ, the apostles went to different lands to spread the Word of God. St. Thomas went east through Babylon, present day Iraq and onto India. On arriving at the Kerala coast in 52AD, St. Thomas reportedly performed a miracle in front of Brahmins taking a ritual bath. He threw the water in which the Brahmins were bathing into air and it stayed there (Chittilaphilly, 2000:14). Then, The Brahmins impressed by this miracle, immediately asked to be baptized. St. Thomas established churches at Kottaickal, Kokamangalam, Paruetta, Chayel, Kurukkanikulam, and Palloor. He also established chapels and erected crosses at Niranam, Pallipooran, Vattamarry, Cranganore, Palloor and Kuthamana before he was martyred outside Chennai. During St. Thomas‘s tenure in Kerala, he performed miracles and acts of penance that draw pilgrims to St. Thomas sites to this day (Sonja, 2011: 31). “When I was young, low-castes had to get out of the way of an upper-caste. They would know to get out of the way because the upper-caste would travel with a servant. Every now and again, the servant would call out “hoi”. When I was a young girl, I would hear that. “Hoi…” and then a little while later, “hoi”. If the low-caste was on the path, he would hide off the path until the upper-caste passed. They used to get out of our way too. My mother told me that us Christians would have servants to sweep the ground before us as we walked so we would not step on any bugs. We were just like upper-caste Hindus” (Sonja, 2011: 36). Restrictions were also placed on worship—lower castes were not permitted to worship the ‘high‘ Hindu Gods (Shiva, Vishnu, and Krishna) but were relegated to demon worship. Temple entry for low-castes was denied. Low-caste Hindus and Christians were prevented from obtaining and education and excluded from public service and government positions (Sonja, 2011: 36). Namboodiriswere exempted from land taxes while low-castes had to pay taxes and fees for even the right to use an umbrella or a palanquin. Namboodirisalso controlled the informal judicial system. While they were exempted from the death penalty, low-castes could receive the death penalty for ordinary offenses such as theft. The sentences of low-caste criminals were brutal: death by elephant trampling, blown from mouth of cannon, hung for 3 days, and mutilations (Sonja, 2011: 36). Historians have conjectured that regulating the oldest son to marry within the caste ensured that the illam(Brahmin property/residence) was kept caste pure (Sonja, 2011: 38). Only converted upper-caste Hindus would be accepted as part of the Syrian Christian fold (Palakunnel, 1999: 221). THE UPPER CLASS Characters who are Upper Class in the God of Small Things are: Pappachi, Mammachi, Chacko, BabbyKochama, Estha and Rahel. The novel tells us about social life in Ayemenem, a rural area in Kerala, India. Pappachi is one of the richest people in the area. He lives in a good wealth. Every single thing that he does shows that he is a rich person. Thus, Pappachi belongs to the upper social class. The higher class people, such as working class women or women who has rich husband usually have a higher life-style. It can be seen from the way of their life. Appearance becomes the most important thing for upper class women. They usually wear expensive clothes or expensive stuff to show off to other people that they are upper class. Mammachi here, in the novel, in the reality of the novel, is told as the wife of Pappachi, a Syrian Christian with high social class. Becoming a wife of the man from high class, indirectly, will lift up her status in front of the society’s eyes. With that fact, Mammachi “should” have a life as upper class, with glamour life style, exclusive life, and everything with highest quality. Expensive, that is the proper word for her jewelries, as been exposed to this statement, “Margaret Kochamma took Mammachi’s hand. The fingers were soft, the ruby rings were hard” (Roy, 1997: 83). There, the fact is barely exposed, how Mammachi’s passions and desires toward jewelries, especially for the expensive ones. Wherever her body exists, wherever her feet step up, wherever her life strolls up to her social life, the jewelries never go to waste to be leaved, it is always following to decorate herself to become “like” upper or high class as usual. Probably, it can be related to the characteristics of women universally, that they likely to show off their jewelries to appear the impression of their status, class, and wealth. Chacko is the first child of Pappachi. As the oldest child, plus a fact of his sex is men, Chacko has privilege. Furthermore, in India, men are having high position especially in social life. It can be understood that India is Patriarch Country where men must have privilege to control everything including women. Going back to Chacko’s fact, in the family system, Cahcko can claim to own all properties in the family. As Mamachi’s Pickles company, the controller, the manager, the one who has major right is the oldest men child, and he is Chacko, it can be read on this statement, “Legally this was the case, because Ammu, as a daughter, had no claim to the property” (Roy, 1997: 28). Based on that fact, it can be supposed officially that Pappachi’s and Mammachi’s wealth will be inherited on Chacko, while Ammu, as the women child, has no right on that privilege above those wealth or properties. It presents that Chacko has a govern of Pickles Factory. It is strengthened with the statement of Chacko confesses that the factory is his own. That is clear factually that Chacko has good wealth that means he is a high-class man. Actually, it is important to add that Chacko also has a potential to manage the factory because Chacko has been educated, he has good level of education. Thus, it drives his brain being clear of thinking cleverly, managing something in a god way, and giving good profit. For additional information that supports it, “Chacko had been a Rhodes Scholar at Oxford and was permitted excesses and eccentricities nobody else was (Roy, 1997: 19). Baby Kochama is the sister of Pappachi, John Ipe. She is the most famous person in Kerala. “He was a priest of the Mar Thoma church. Reverend Ipe was well known in the Christian community as the man who had been blessed personally by the Patriarch of Antioch, the sovereign head of the Syrian Christian Church—an episode that had become a part of Ayemenem’s folklore” (Roy, 1997: 12).John Ipe is not common priest, she becomes famous because she has been blessed personally by Patriarch of Antioch. Patriarch of Antioch is the Head of Christian Syrian Church. Because of that, after John Ipe has been blessed by the the Head of Christian Syrian Church, John Ipe is respected by the people around her. It means that John Ipe has high social class, especially for people in Ayemenem. Ammu is the last child from Pappachi’s family. As the child of high-class family, Ammu automatically belongs to be high-class one. Her life, lifestyle, and education have shown that Ammu is high-class one. Education is something important for a one with high social class. It is usually considered as he step of a one to be high-class one. It is also a factor that can support a one to be high-class one because it can influence the sight and the view of people around him or her to consider as high-class one. Ammu is drawn as a woman that has good education, this educated woman continuously affects her status. It is seen by this statement, “Ammu finished her schooling the same year that her father retired from his job in Delhi and moved to Ayemenem.” (Roy, 1997: 19). After finishing her education, Ammu marries to someone. Ammu marries to someone with good wealth. Ammu meets with her husband in a party, the party where rich men jostle and show their wealth off. It is accepted when it is called as a party where rich men assemble, because the irrational thing must be happening when the party is for poor men or low class because the Touchable and the Untouchable must not be touched each other. While Ammu is high-class one, and she comes to a party. The party logically must be a party for high class, and the man that marries to Ammu must be a man from high class. Several weeks pass, Ammu marries with him. “He was on vacation from his job in Assam, where he worked as an assistant manager of a tea estate. His family was once-wealthy zamindars who had migrated to Calcutta from East Bengal after Partition.” (Roy, 1997: 19). THE LOWER CLASS Characters who are Lower Class in the God of Small Things are: Velutha, Ammu, Estha and Rahel. Lower social class in this novel is strongly drawn in Velutha’s character. Velutha is black but he is so smart. Social class rises strongly through his life. He lives in poverty. As the main character, Velutha belongs to the lower social class. Life background has significance role and it makes his having lower class level as poor people. “He was called Velutha-which means White in Malayalam-because he was do black. His father, Vellya Paapen, was a Paravan. A today tapper (Roy. 1997: 35).The quotation shows Velutha’s life background. Velutha is a son of Vellyan Paapen whom a Paravan. So, it automatically makes Velutha become a Paravan too. Paravan is the lowest caste in India. It is also called Untouchable. A Paravan contains of poor people because usually Paravan only work as a lower labor. Velyan Paapen works as a maid in Pappachi family, it means that he cannot deserve his son to get a good financial condition. It brings Velutha living under poverty. Social class rises through his poor condition, because the economic condition he has, indicates that Velutha belongs to lower class people. Ammu is a Christian Syrian from upper class. However, after she gets a divorce with her husband, her status also changes. From being a high class, he turns it in to lower class. After divorcing, Ammu comes back to Pappachi’s home in Ayemenem, Pappachi welcomes it because of his compassion toward Ammu, his daughter. But, it does not take to many time for Ammu to decide to get off of the home. Because Ammu “secret” love with Veluthe has been revealed up, thus it drives Pappachi angry and Ammu gets off. Ammu has to fulfill all necessity for her life, she has to work to earn money. Before that, she works at the Pickle factory of her family, but when she has been dropped out of her home by Pappachi, Ammu search for other job in other place. Job is the important factor in dragging the strata in front of the eyes of society socially. People from high class usually have prestige job with good salary. Because it can influence to what life they choose, by buying everything, shopping everything, and establishing their arrogance of the wealth. Following that, the impression of being an upper class can be sought and decided. However, behind that fact, the lower class only has lower jobs, those lower jobs jail their economy. The limited economical conditions will never change their status and strata in front of the society’s eyes, thus, their status will keep being lower and never being changed. Ammu, then decides to work at a hotel as a receptionist, and working as a receptionist is not a prestige one. Additionally, the hotel is not five stars hotel, it is only a small hotel with low standard, as has been quoted on this statement, “Ammu had lost the latest of her succession of jobs—as a receptionist in a cheap hotel—because she had been ill and had missed too many days of work.” (Roy, 1997: 76). Nevertheless, working here has dropped the health of Ammu down. Probably, it is caused by her changing life, from living in good house with good treatment to living in a low life. His illness finally sharpens to the way she works, she often gets the absences on working, and it makes her getting the fire as a receptionist in that small hotel. Furthermore, working at a small hotel will not give gret significance of changing for a woman like Ammu, particularly for what she gets on his salaray. This quotation can be regarded, “On that last visit, Ammu spent the morning with Rahel in her room. With the last of her meager salary she had bought her daughter small presents wrapped in brown paper with colored paper hearts pasted on.” (Roy, 1997: 77). ‘Meager salary’ explains clearly how small the salary that ammu gets, and it must not fulfill enough for her necessity. The work of Ammu like this is not the prestige one and the salary is too small. That is the main point of this talk, it is concluded that Ammu becomes a lowe class after facing divorcing. The divorcing is added by her love with a low class, Velutha, that facts slap her status in front of the society. Socially, her status collides and becomes one of low class masses. Estha and Rahel are the twin of Ammu with Baba. Estha and Rahel have unique life in this novel. When they are still child, Estha and Rahel are treated by Ammu in her family life that is from upper class. However, although they are live there, there is an unsaid rule that sets Ammu and her children have no right anymore to live in Pappachi’s house. But, Pappachi’s commission breaks that rule, so that is why they can still enjoy to live in Pappachi’s house. It is clear to be understood that Estha and Rahel can be put in to a detail that they are children from upper class. Estha and Rahel can enjoy a trip with family private car that for low class that is the most greatful trip. The trip that they will ever enjoy. The trip they never imagine. The trip they never fantasize because they have been adapted to jostle in the public transportation with the bad smell and disgusting sweat of poor people. Their life is painted in that public transportation and tripping with privacy car is only a part of their fantasy. Estha and Rahel also often go to cinema, it is even told that they have watched film entitled “The Sound of Music” three times. After watching it, they go home to Ayemenem, with one night over sleep in a great hotel. Plus, the smell of food, their trip becomes perfect. The fact like that, is something that is only for upper class, it is important for low class of having it. This lifestyle, indeed, need much money, thus it belongs to upper class with good condition economically, besides that, it is also becomes the viewpoint of valuing the strata of a class. Rahel is a daughter of Ammu. After being left by her brother, Estha, who is sent back to his father, Rahel becomes sad, the sadness grows peaking up when she has to be leaved by Ammu. Rahel, then is treated by Mammachi. All the need of Rahel is fulfilled by Mammachi. As the grand daughter who grows in upper class family, Rahel gets good education. “She spent eight years in college without finishing the five-year undergraduate course and taking her degree. The fees were low and it wasn’t hard to scratch out a living.” (Roy, 1997: 9). Rahel then continuous her school to a university, and it is not a big problem for Mammachi to pay all the charge of the school. Rahel spends eight years in that university and ends it with no graduation, or it means that Rahel drops out. She even decides to marry to a man from America and go with him to America. Actually, that is not good marriage for Rahel. She is too hurry up to marry. “Rahel drifted into marriage like a passenger drifts towards an unoccupied chair in an airport lounge. With a Sitting Down sense.” (Roy, 1997: 10). After deciding to marry and move to America, Rahel does not enjoy her life, because she is not treated as an upper class. Because Rahel has married, her life burden goes to her husband’s own. Thus, Mammachi does not pay anything of Rahel’s life anymore. However, the age of the marriage is too short, not long after that, the marriage is broken down. Rahel divorces with her husband, and it insists Rahel to work to stay alive and fulfill all necessity for her life in America. It is clear to see that Rahel live in the circle of low class life. She works as a waiter in an Indian restaurant in New York. It is easy to be classified that working as a waiter is one of low class job, it has no any prestige. That job just give little earn for her life daily. Life he has to pass is different with the life he gets in Ayemenem. Rahel also ever works as an employee in a gas station. This job is not a job that can give her good earn in salary. This fact, one day, makes a procure offers Rahel to become a sexual worker where she can get more money. This is simply clear to understand, how low Rahel life in America, and she can be put in to one of low class people. THE IMPACT OF THE SOCIAL CLASS In this section, the impact of social class will be explained. The impact of the social class will be revealed through several characters that have connection each other. The consequences of social class by Henslin (2003) will be used to analyze the impact of the class. The consequences of class that will be used to explain are family life, education, religion, and criminal justice system. Pappachi, the character who is drawn as Upper Class has some impact in his social life. Those are family life and mental health. Papachi has good education, he has prestigious job, besides that, he also has good wealth. It makes him becomes a character or a one who is upper class. The wealth and the prestigious job he has makes him always looks prefect. He desires to be looked as the perfect one around the people. As a man with upper class, Pappachi becomes very famous in Ayemenem. It can be seen to the quotation above, when Pappachi passes away, Indian Express, a newspaper with English letters, writes the news about the death and the funeral of Pappachi. It means that, Pappachi is not only an upper class one, he is more than that. However, the important part that can be informed in this fact is, the class of Pappachi. It is not easy for low class to be put on the newsletter, only important information that can be considered as the important news to be informed, and low class does not belong to. Mammachi is an Indian woman character. As an Indian woman, Mammachi receives all things happen to her. Mammachi marries to Pappachi who is an upper class. Thus, it can be seen that it is not easy to have a couple from different class, especially upper class. However, Mammachi has been ready of facing all the risks, the risks that bring the consequences of social class.Mammachi is accustomed to get hit from Pappachi. Mammachi does not do anything because for Indian women, women, as a wife,have to serve their husband. So whatever her husband does to his wife then his wife must accept it. “He never touched Mammachi again. But he never spoke to her either as long as he lived’ (Roy, 1997: 23). So, Mammachi is never really touched or talked at all to Pappachi until Pappachi died. Besides family life, Consequence of social class also influences to the religion. People who are Christian Syrian, are supposed to be upper class than Hindus. In an intriguing chapter of Modernization and Effeminization in India, Anna Lindberg discusses how jobs within cashew factories in Kerala are dependent on one‘s caste. The dirtiest job, shelling the cashews, is done by the lowest castes of the factories. Shelling is the most unhealthy job as it involves removing the roasted nuts from the corrosive black oily shells. The next step up is peeling, or removing the brown skin from the cashews and is performed by both the scheduled castes and the Ezhavas caste (Linberg, 2005: 55). That quotation explains indirectly how caste affects the job of people in India. People with upper caste will throw the obligation and duty of the job to the lower caste, and people with upper caste prefer choosing clean and light works. Thus, the lower caste, people with the lower caste always works with dirtiness job, and low class job. Chacko is the first son of Pappachi and Mammachi. He was born from upper class family, and it makes the life of Chacko is surrounded by the wealth that can sink himself in the sea of this life. Upper class is portrayed clearly in this novel and it is reflected by Chacko’s character. It can be looked at the background of education and of lifestyle of Chacko. The background of education of Chacko that is laid on Oxford and marries-divorces-re-marries, and gets back to Ayemenem, and ends it with heading the Pickle factory, have proven that it is the interesting life to have. However, this social class, finally affects his mental health. As the head of the Pickle factory, Chacko actually can do everything he wants, he has that chance. As has been exposed on this follows statement, “He would call pretty women who worked in the factory to his room, and on the pretext of lecturing them on labor rights and trade union law, flirt with them outrageously.” (Roy, 1997: 31). Chacko has a habit of calling all beautiful women who work at the Pickle factor. He invites them with reason to teach them about the rights they have to have. However, Chacko does not do that, it is just a reason. Chacko tries to sleep those women with giving them money. For Chacko, spending much money for sleeping with women, is not a great problem. The condition of his economy, especially money, can guarantee it. Baby kochama is a character who has upper social class in the novel. Her social class then gives impact toward criminal justice system. One with upper social class is usually respected. Once, when Baby Kochama arrives at a police station, she is treated as if a queen. The police treat her very well, with great attitude, and so much respect that is never hidden in the police’s mouth. She ever sells a lie to the police, and the police trust it by taking it for granted. Based on that fact, it can be articulated that the impact of Baby Kochama as the upper class is really affecting to her life, her life that is full of respect by the people or the society around her. For the support to proof it, this statement can be supposed to, “Baby Kochamma misrepresented the relationship between Ammu and Velutha, not for Ammu’s sake, but to contain the scandal and salvage the family reputation in Inspector Thomas Mathew’s eyes.” (Roy, 1997: 122). It is clear when it is known that Baby Kochama sells the lie to the police just because she does not want her family gets down of reputation. The way Baby Kochama utilizes her status in the society is very tricky. She reconstructs the story of Ammu and Velutha because the relation between the two is such a shame thing for the family, especially for Baby Kochama’s family that is from upper class. With no having any choices to save the reputation, Baby Kochama finally does the lie, with regardless the value of lying is lower than lower class status. Impact of Ammu as lower social class is drawn in physical health and criminal justice system. Ammu suffer from many diseases after he gets out of Ayemenem’s house. As has been exposed on this follows statement, “Who came back to Ayemenem with asthma and a rattle in her chest that sounded like a faraway man shouting” (Roy,1997: 76). Her weak economical condition grave illnesses suffered by Ammu. There is not much that can be done by Ammu. Eventhought she is sick, she still has to work to meet all her needs. Living in poverty make Ammu can not treat her disease. Her physical changes occur from groomed Ammu and beautiful become Ammu who has disease and ugly. Ammu physical changes that profoundly changed drastically make her looks very different. When Baba, who is a Hindus, marriage with Ammu that makes the church doesn not want to bury Ammu. because for the church Ammu has different class from them. So, Chacko dicides to bring Ammu’s bodies to the electric crematorium. Ammu’s bodies are treated very badly, they wrap the body of Ammu on a dirty mattress. How Ammu’s bodies are treated very clearly illustrates how Ammu’s social class. Her marriage that is considered wrong, living in poverty and disease she has, it all led to Ammu suffer until she dies. Cremation place that is used to burry Ammu’s bodies is very dirty. From the above quotation clearly seen what people is burned in that place. Only the bodies of beggars, criminals and police custody are burned on the ground. It is impossible for bodies of people wiyh high social class and have good econmomic condition is buried in that ground. Unfortunately again, no more families are present in addition to the ground except Chacko and Rahel. Impact on the character Velutha great looks of the criminal justice system. Velutha as a lower social class is treated badly in the criminal system. When velutha is accused of making a mistake then the police catch him in a bad way. They do the violence which is not a procedure of arrest. They woke Velutha with their boots (Roy, 1997: 144). The police wake Velutha who is asleep with their hard shoes. The police do not want to touch velutha because he is a lower class. Velutha gets injustice. The police directly commit violence on Velutha without asking first what happen actually. On Estha’s character, social class gives impact on his mental health. Estha who is accustomed to luxury living in Ayemenem’s house. One day he has to move because his mother send him bank to his father. Where the condition of his father is different with condition in Ayemenem’s house. Estha finished school with mediocre results, but refused to go to college. Instead, much to the initial embarrassment of his father and stepmother, he began to do the housework. As though in his own way he was trying to earn his keep. He did the sweeping, swabbing and all the laundry. He learned to cook and shop for vegetables (Roy, 1997: 6). His mental health is disturbed after he decides not to continue his education into college. Estha starts doing what he should not do. He does all the homework that should be done by women. And since then Estha starts rarely speak until one day he really stop talking altogether. Estha performs regular activities without spending a single word. He does not care what the people around him are doing. He will still silent. Although his twin sister, Rahel, is next door and talk, then Estha still keep silent. This condition sometimes makes Rahel think whether Estha become mad, as has been exposed on this follows statement, “Had be seen her? Was be really mad? Did be know that she was there? They had never been shy of each other’s bodies, but they had never been old enough (together) to know what shyness was” (Roy, 1997: 44).EStha’s mental condition shows that social class can also give impact on mental health. Rahel is raised by mammachi after Ammu die. Of course being raised by mammachi will make life in very good socio economic condition. Raised by Upper class lifestyle makes an impact on family life of rahel. Rahel who has been abandoned by both parents become a very naughty girl. Because she never get a good attention from all her family. Uncle Chacko and Mammachi just give her all the material only. Rahel gets all the facilities that she need so she can reach high education. it is clearly explained how Rahel who are not given attention by all her families. They are just busy with their own affairs without considering the love that needed by Rahel. She is just given all the material she needs such as clothes, food, and money. That all makes Rahel become a naughty girl. Rahel is actually a beautifull smart kid, but she often makes the act that make her eventually are punished and expelled from the school. In the above quotation illustrated how Rahel delinquency in schools. Rahel is first convicted when she is at the Convent of Nazareth. She is caught decorate dorm room door with a flower head. And the next day she is tried and given punishment by the head monastery. Six months after, Rahel is expelled from school because she is already given many punishments and she still keeps naughty. It is all because of Rahel ever caught smoking, she also ever steal and burn bun of Houseministers. Rahel becomes naughty because of she never gets a good attention. Here, it clearly shows that social class olaso give impact to family life. Rahel eventually grows into adulthood without attention and affection of a family. As an Indian women, Rahel’s future is determined also by her marriage. CONCLUSION Based on the recent analysis of the data, the result can be concluded that all the issues that have been revealed by statement of the problem can be drawn. There are two conclusions which can be concluded. The first is about the depiction of the social class, the second is about the impact of the social class on the character. The first conclusion is about the existence of social class experienced by the character in the novel. Karl Marx divides social class into two classes. They are Capitalist class (Upper Class) and Working Class (Lower Class). The existence of social class can be seen by wealth, occupation and educational level. As Worsley says that each of the aspects can be used for different purposes or they can be combined. So the character in the novel is divided into two classes. Upper class’s characters are Pappachi, Mammachi, Chacko, BabyKochama. And the lower class’s characters are Ammu, Velutha, rahel and Estha. The social class can be identified by their economic background, their way of life, their way of dressing, and the standard of living. The second conclusion is about the impact of social class on the character. The impacts of social class are divided into six categories. They are: physical health, mental health, family life, education, religion, criminal justice system. Every character has different social class impact. Furthemore, the writer also find some characters who have different social class. Here, Ammu, Rahel and Estha are Upper social class. Because of some problems, their social class is changed from Upper social class to Lower social class. And it also makes different impact for them. REFERENCES Abrecombie, Nicholas. et al,. 1994. The penguin dictionary of sociology (3rd edition). New York: Penguin Books Ltd. Al-Qudaeri, Golam Gaus & Muhammad Syaiful Islam. 2011. “Complicity and Resistance: Women in Arundhati Roy’s The God of Small Things”. ISSN No. 1948-1845 (Print); 1948-1853 (Electronic). Ambedkar, BR. 1916. Caste in India: their mechanism, genesis, and development. Julundur City: The Awami Press. Chittilapilly, Paul. 2000 The Life and Nature of the St. Thomas Christian Church in the Pre-Diamper Period. Kochi: LRC Publications. Chu, Yu Ru.2006. Recasting India: Caste, Trauma, and the Politics of Transgression in Arundhati Roy’s The God of Small Things. Hegel, Georg Wilhelm Friederich. 2001. The Philoshopy of History. Ontario: Batoche Books. Henslin, James. 2003. Sociology. Boston: Pearson. Hornick, Barbara. 2011. Sociology Reference Guide: Defining Class. New Jersey: Salem Press. Keane, David. 1978. Caste-based Discrimination in International Human Rights Law. Hampshire: Ashgate Publishing Limited. Khori, Moh. 2010.Social Class and Political Satire in Mark Twain’s The Prince and The Pauper. Lawrence, Wishart London. 1965. V. I. Lenin: Collected Works Vol. 29. Moscow: Progress Publisher. Mines, Diane P. 2009. Caste in India. Michigan: Association for Asian Studies, Inc. Narwoko, Dwi., Bagong Suyanto ed,. 2007. Sosiologi: Teks Pengantar & Terapan. Jakarta: Kencana Prenada Media Group. Nanda, Silima. 2012. “Women as the Oppressed in The God of Small Thing”. ISSN 0976-8165. Neil, Stephen. 1984. A History of Christianity in India. Cambridge: Cambridge University Press. Nobs, Jack. Et al,. 1980. Sociology. London: Macmillan Education Ltd. Palakunnel, John. 2003. Christianity is Truly Indigenous inSt. Thomas Christians. Kochi: LRC Publications. Rao, Anupama. 2003. Introduction in Gender and Caste. New Delhi. Kali for Women. Renou, Louis. 1961. Hinduism. New York: George Braziller, Inc. Richards, WJ. 1908. The Indian Christian of St Thomas. London. Bemrose& Son Limited. Roy, Arundhati. 1997. The God of Small Things. London: Flamingo Taylor, Richard.1981. Understanding the Elements of Literature. New York: Palgrave Macmillan. Thomas, Sonja. 2011. From Chattas to Churindas: Syrian Christian Religious Minorities in a Secular Indian. New Jersey: The State University of New Jersey Wellek, Rene., Austin Warren.1984. Theory of Literature. New York: Mariner Books Worsley, Peter. 1970. Introducing Sociology. Baltimore: Cox & Wyman Ltd.